Exchange-biased magnetic tunnel junctions with antiferromagnetic epsilon-Mn3Ga - RODE, KARSTEN; VENKATESAN, MUNUSWAMY; STAMENOV, PLAMEN; COEY, JOHN (My University, 2012)
Oriented c-axis films of the hexagonal triangular antiferromagnetic ?-Mn3Ga have been used in bottom-pinned synthetic antiferromagnetmagnetic tunnel junctions with MgO barriers, which show up to 150% tunneling magnetoresistance at room temperature.Exchange bias fields as high as 150?mT can be achieved for samples field-cooled from 100??C. Thin films of the antiferromagnet have a Neel temperature in excess of 650?K and provide an interface exchange energy with CoFe of 0.09 mJ m?2. They show an isotropic uncompensated magnetization of M s?=?48?kA m?1, with a coercivity? 0 H c > 3?T.
PUBLISHED
Keywords: Physics